Tracking the impacts of climate change on human health via indicators: lessons from the Lancet Countdown - Di Napoli, Claudia; McGushin, Alice; Romanello, Marina; Ayeb-Karlsson, Sonja; Cai, Wenjia; Chambers, Jonathan; Dasgupta, Shouro; Escobar, Luis E.; Kelman, Ilan; Kjellstrom, Tord; Kniveton, Dominic; Liu, Yang; et al. (BMC public health, 2022)
In the past decades, climate change has been impacting human lives and health via extreme weather and climate events and alterations in labour capacity, food security, and the prevalence and geographical distribution of infectious diseases across the globe. Climate change and health indicators (CCHIs) are workable tools designed to capture the complex set of interdependent interactions through which climate change is affecting human health. Since 2015, a novel sub-set of CCHIs, focusing on climate change impacts, exposures, and vulnerability indicators (CCIEVIs) has been developed, refined, and integrated by Working Group 1 of the “Lancet Countdown: Tracking Progress on Health and Climate Change”, an international collaboration across disciplines that include climate, geography, epidemiology, occupation health, and economics.
Gesehen am 18.05.2022